Mathematics Anxiety, Resiliency, and Chemistry Performance of Grade 9 Students - Ledesma, Jembee; Linaugo, Joji (Technium Social Sciences Journal, 2023)
While Mathematics is a necessary component of Science, many students enter scientific courses with minimal arithmetic skills. This descriptive-correlational study examined the relationship between Grade 9 students’ Mathematics anxiety and resiliency to their academic achievement in Chemistry. Data was collected from the 302 participants drawn from the total population of 1,394. A three-part, fully adopted questionnaire was used. Descriptive scores were analyzed and interpreted using mean and standard deviation. To test for significant differences in the aspects of the dependent variables, Mann-Whitney U was used, and Spearman’s rho correlation was used to test for significant relationships. Results of the study revealed that the level of Mathematics anxiety of the Grade 9 students was on the "average". On the other hand, the level of Mathematics resiliency of the Grade 9 students was “high”. The study also reflected that Grade 9 students were proficient in Chemistry. Mathematics anxiety and resiliency do not correlate with Grade 9 students’ academic achievement in Chemistry. Anxiety and resiliency of Grade 9 students towards Mathematics do not affect their ability to acquire knowledge in Chemistry. Student experience of Mathematics anxiety is not closely related to their academic achievements. It is recommended that schools provide opportunities for students to cultivate more positive attitudes toward Mathematics.